Atenolol’s Inferior Ability to Reduce Central vs Peripheral Blood Pressure Can Be Explained by the Combination of Its Heart Rate-Dependent and Heart Rate-Independent Effects - Tuuli Teeäär; Martin Serg; Kaido Paapstel; Mare Vähi; Jaak Kals; John R. Cockcroft; Mihkel Zilmer; Jaan Eha; Priit Kampus (International Journal of Hypertension)
Objective. Whether the inferior ability of atenolol to reduce central (aortic) compared to peripheral (brachial) blood pressure (BP) is related to its heart rate (HR)-dependent or -independent effects, or their combination, remains unclear. To provide further mechanistic insight into this topic, we studied the acute effects of atenolol versus nebivolol and ivabradine on systolic blood pressure amplification (SBPA; peripheral systolic BP minus central systolic BP) in a model of sick sinus syndrome patients with a permanent dual-chamber cardiac pacemaker in a nonrandomized single-blind single-group clinical trial. Methods. We determined hemodynamic indices noninvasively (Sphygmocor XCEL) before and at least 3 h after administration of oral atenolol 50 or 100 mg, nebivolol 5 mg, or ivabradine 5 or 7.5 mg during atrial pacing at a low (40 bpm), middle (60 bpm), and high (90 bpm) HR level in 25 participants (mean age 65.5 years, 12 men). Results. At the low HR level, i.e., when the drugs could exert their HR-dependent and HR-independent effects on central BP, only atenolol produced a significant decrease in SBPA (mean change 0.74 ± 1.58 mmHg (95% CI, 0.09–1.40; P=0.028)), indicating inferior central vs peripheral systolic BP change. However, we observed no significant change in SBPA with atenolol at the middle and high HR levels, i.e., when HR-dependent mechanisms had been eliminated by pacing. Conclusion. The findings of our trial with a mechanistic approach to the topic imply that the inferior ability of atenolol to reduce central vs peripheral BP can be explained by the combination of its heart rate-dependent and -independent effects. This trial is registered with NCT03245996.